Aktivitas Public Relations Dalam Upaya Meningkatkan Citra Taman Wisata Candi Borobudur - Julita M.A. Raturoma; Lina Sinatra Wijaya (Universitas Multimedia Nusantara, 2018)
Indonesia is one of the world's tourist destinations. Therefore, Indonesian tourism must be built and developed. Taman Wisata Candi (TWC) Borobudur, as one of the tourist attractions with its beauty and grandeur, becomes the main attraction for all people. The purpose of the research is to find out whether public relations activities conducted by the TWC can increase the image of the temple or not. This is a descriptive qualitative research. The data was gathered through interview and observation. The sources of this research were visitors and public relations officer of TWC. The result of this research shows that the internal activities conducted by public relations officer of Taman Wisata Candi Borubudur such as employee relations, field trip, internal magazine, personal contact and sport, made the employees felt appreciated and cared and this indirectly creates a sense of belonging from the employees towards the institution. The external activities conducted, such as customer relations, community and pers relations, indirectly influenced the visitor perceptions towards the image of TWC Borobudur in terms of service to the community and also improve the relationship with media. It shows that the internal and external activities carried out by the public relations of TWC Borobudur give positive impact and indirectly improve the image of TWC Borobudur among the society. Keyword: public relations activities, image, travelling and Borobudur temple